Factors Influencing Practice of Obstinance from Sex Among Students at Zingwangwa Secondary School - Chiumia, Jacob S (Kamuzu University of Health Sciences, 2022)
Young people represent almost half of all HIV infections worldwide. It is estimated that 1000,OOO adults and children are living with HIV/AIDS in Malawi. (National AIDS Commission, 2006). Despite education on abstinence and government's effort to combat HIV/AIDS, a lot of the youth get infected with HIV through sexual intercourse and also drop out from school due to unwanted pregnancy. These youth start sex at age younger than 12 years. The purpose of this quantitative study was to explore factors influencing practice of abstinence from sex as a method of HIV/AIDS prevention among secondary school students. Ethical consideration was achieved by obtaining permission from responsible boards and through informed consent from the subjects. A sample of 30 students which consisted of 15 males and 15 female from Zingwangwa secondary school located in Zingwangwa Township in Blantyre District was chosen. A questionnaire was used to collect data from subjects. The questionnaire was in English. Stratified random sampling was used to obtain the subjects of the study.